SARS-COV-2 Vaccination and Employment: the Legal Framework in the EU and Hungary - Földes, Mária Eva; Kaposvári, Csilla (Medicine, Law & Society, 2021)
The paper explores whether and under what conditions, vaccination against SARS-CoV-2 may become a mandatory requirement for employees. It includes a discussion on EU action on SARS-CoV-2 vaccination and its relevance for national level policy with emphasis on the legal basis and instruments used by the Union to persuade national authorities into action to increase vaccination uptake. The analysis then moves to the national level by focusing on the case of Hungary. Following an overview of the legal and regulatory framework for SARS-CoV-2 vaccines deployment, the analysis zooms into the sphere of employment and explores whether and how the SARS-CoV-2 vaccination may be turned into a mandatory workplace safety requirement. The paper highlights the decision of the Hungarian government to introduce compulsory vaccination for employees in the healthcare sector, and concludes with a discussion of the relevant rules and their potential, broader implications.